Análisis estadístico de la ocupación hotelera en la ciudad de Babahoyo - FRANCO RAMOS, CARLOS ALFREDO (2024)
This case study has as its theme: "statistical analysis of hotel occupancy in the city of Babahoyo", its general objective was to determine hotel occupancy in the city of Babahoyo through a statistical analysis, seeking to comply with the research line of tourism planning and management. The methodology applied in this case study was descriptive and documentary, with a quantitative approach. The technique for data collection was the survey, whose instrument was the questionnaire, the results obtained showed that there is a correlation with the increase in tourism demand when there are cultural and sporting events, among others in the canton, as well as that the quarter with the highest demand is between the months of October to December and the lowest demand in the quarter from January to March. In conclusion, hotel occupancy in Babahoyo needs the development of strategies to promote the tourist, ecological and gastronomic attractions, with the development of events that attract the attention of tourists and travelers of the town, as well as to generate a guide that provides information in hotels so that guests know about the tourist attractions of the canton and how to acquire these plans